Hubungan Motivasi Dengan Kinerja Perawat Di Ruang Rawatinap - Taleetha Kinan Yulia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
A hospital is an institution or health service organization with broad and comprehensive functions, dense in expertise and capital intensive. Hospitals carry out broad functions so they must have resources, both capital and experienced and professional humans. Nursing service is part of the health service system in hospitals which has the function of maintaining the quality of service, which is often used as a barometer by the community, in assessing the quality of hospitals, thus demanding the professionalism of nurses in their work as shown by the results of the performance of nurses, both implementing and nursing nurses. management in providing nursing care to clients. Maximum implementation of nurse work in quality health services occurs when the nursing care implementation system supports professional nursing practice according to standards (RI Law No. 38, 2014). Motivation is the factors that exist within a person that move and direct his behavior or encouragement that causes him to do something or do something to satisfy individual needs to achieve certain goals (Rini, 2015).